Tube Blockage Solutions for Industrial Heat Exchangers: Solusi Penyumbatan Tabung untuk Penukar Panas Industri - Ferdiansyah, Faris; Firdaus, Rachmat (Procedia of Engineering and Life Science, 2024)
This study investigates the root causes of blockages in heat exchanger tubes and proposes effective mitigation strategies. Industrial heat exchangers face recurrent challenges from tube blockages, impairing operational efficiency. Through a combination of experimental analysis, computational modeling, and data-driven approaches, the research identifies the role of contaminants in causing pressure drops and outlines targeted maintenance protocols. Findings underscore the significance of proactive measures in optimizing heat exchange processes, offering valuable insights for enhancing system performance across diverse industrial applications. Highlights: Tube blockages disrupt production efficiency. Pressure drop due to blockages affects system performance. Analysis needed for prevention measures. Keywords: Production Process, Blockage, Exchangere